Prenatální růstové křivky české populace - Polášková, P; Kuběna, A; Calda, P (Ceska gynekologie, 2014)
OBJECTIVE: Determination of ultrasound biometric parameters of fetuses in the Czech population during pregnancy. METHODS: We retrospectively analyzed a data set of 20,566 pregnant women from the years 2008 to 2012 who met the following inclusion criteria: Caucasian ethnicity; measured biometric parameters biparietal diameter (BPD), head circumference (HC), abdominal circumference (AC), femur length (FL); body mass index (BMI) of the pregnant women < 35 kg/m2.We excluded pregnant women with multiple fibroids distorting the uterine cavity; pathologically developing fetuses; and pregnancies where we were not able to verify the correct dating. We did not carry out selection as to the method of getting pregnant. The pregnancy age was from 19+0 to 42+6 gestation weeks. As in all studies, the age of pregnancy refers to the completed gestation weeks (for instance 23+0 to 23+6 = 23rd gestation week). We then compared our newly derived growth curves with the curves currently used, for BPD, HC, AC, FL and EFW, in the 3rd or 5th percentile, 50th percentile and 95th or 97th percentile (according to data obtained from reference studies). RESULTS: The study included 40,806 observations. The number of observations exceeded 500 in all weeks except in the 42nd week. The median age of the pregnant patients was 31.9 years (min 14.9, max 52.54). In the studied group we found a lower degree of variability in all parameters. The biometric parameters had higher values for the gestation week than the reference parameters. The estimated weight of the fetuses in our group on the level of the 3rd percentile was significantly higher than the reference value. DISCUSSION: The study was based exclusively on sonographic measurements. Although we excluded from our group intrauterine pathologies that could affect the physiological growth of the fetus, we did not carry out an additional selection using information on the pathologies of fetuses obtained postnatally. However, as the study contains more than 40,000 measurements, we can assume that such additional selection would have had only a minimum effect on the resulting curve. A section of the fetuses that would have been considered eutrophic according to present reference studies could be considered hypotrophic or small for gestational age (SGA) according to our observations. CONCLUSION: We have obtained new prenatal ultrasound growth curves for the Czech population of healthy developing fetuses. In early gestation weeks, we have found statistically significant deviations from the reference studies. Fetuses in our study have significantly higher weight estimate and show a lower degree of variability compared to the reference studies. KEYWORDS: prenatal, ultrasound diagnosis, fetal biometry, percentile curves, biparietal diameter, head circumference, abdominal circumference, femur length, estimated fetal weight, Czech population.